Self-directed R&D teams what makes them effective? - Taylor, Glenn L.
Glenn L. Taylor, Louis J. Snyder, Keith F. Dahnke, and Gary Kuether present the results of a study showing that clear and important goals, good communication and supportive management are key.
Teams can be used anywhere in R&D, and can function effectively even without training, a study finds. But meddling managers can bring trouble.
Teams are used extensively and successfully in every aspect of industrial R&D. Despite little formal training, both the team members and their sponsors find that the team's output usually meets, and often exceeds, expectations. Clear and important goals, clean communications and supportive management are key factors leading to team success. Meddling managers and fuzzy goals tend to lead to failure. Training, team rewards and recognition do not seem to be central to team effectiveness. Teams like their managers to be accessible and to provide resources and support, but not to dictate how the team should function. These requirements can be difficult to balance, but management nonetheless got pretty good grades from the teams in this study, and the teams got pretty good grades from their managers and sponsors.
Keywords: R&D teams